Zinc oxide nanorods growth by chemical and physical vapour deposition methods for sensor applications / Aimi Bazilah Rosli - Rosli, Aimi Bazilah (2015)
Zinc oxide (ZnO) has gradually become on demand semiconductor electronic devices application such as gas sensor, surface acoustic wave (SAW), solar cells and so on. It is found to be a versatile functional material that has a wide variety of growth morphologies. One of common morphology is nanorods which has been explored in this research. The conductivity and transparency of pure ZnO could be enhanced by doping with Aluminium (Al). Although the ZnO and Aluminium doped-zinc oxide (AZO) nanorods have been acknowledged as semiconductor devices by many researchers, the application of the grown nanorods to the existing commercialized semiconductor devices are limited, probably due to the incompatibility of lab-based wet process with the dry-process of existing complementary metal oxide semiconductor (CMOS) technology based manufacturing. In addition, ZnO functionality as sensing membrane for pH and oxygen (O2) gas sensing have not yet been thoroughly investigated. In this work, metal-catalyzed growth of ZnO and AZO nanorods using thermal vapour deposition (TCVD) and also RF-sputtering were explored. The work also involves characterizing the grown nanorods and optimizing the deposition condition prior to application in O2 gas sensor and extended-gate field effect transistor (EGFET) for pH sensing. Through the investigations, it was found that the ZnO nanorods growth by TCVD is the best when the catalyst annealing temperature was 15 min and the catalyst thickness was 15 nm. It was also found the gold (Au) catalyst was better compared to platinum (Pt) since the growth of ZnO nanostructures is more stable on Au catalyst compare than on Pt catalyst. Therefore,the further investigation on AZO growth by sputtering method was done by implementing the best ZnO nanorods growth parameter obtained from TCVD method. From the results, un-uniform AZO nanorods were grown on 5-nm Au catalyst at the RF power and deposition temperature of 200 W and 300 °C, respectively. The best sample obtain from both deposition were further investigated for pH sensing measurement and O2 gas sensor. From the pH measurement test, it was found that sensitivity of ZnO nanorods sensing membrane is 19.2 mV/pH while AZO nanorods sensing membrane is 58 mV/pH. The sensitivity of AZO nanorods sensing membrane deposited by sputtering is better compared to the ZnO sensing membrane and it was close to the sensitivity allowed by Nerst equation (59.6 mV/pH). From the O2 gas sensing test, the results shows that, the sensitivity of AZO nanorods toward O2 gas flow is higher compared to the AZO thin films.